The correct order for bisecting angle ABC is F D E B C A. Option D
<h3>Steps in bisecting angles</h3>
The steps involved in bisecting angles are;
- Place compass point on the vertex of the angle (point B).
- Stretch the compass to any length that will stay OF the angle
- Swing an arc so the pencil crosses both sides (rays) of the given angle. You should now have two intersection points with the sides (rays) of the angle
- Place the compass point on one of these new intersection points on the sides of the angle. Stretch the compass to a sufficient length to place your pencil well into the interior of the angle, this should be within the rays of the angle
- Place an arc in this interior
- Without changing the span on the compass, place the point of the compass on the other intersection point on the side of the angle and make a similar arc. The two small arcs in the interior of the angle should be intersecting
- Connect the vertex of the angle (point B) to this intersection of the two small arcs
From the listed steps, the correct order for bisecting angle ABC is F D E B C A. Option D
Learn more about bisectors here:
brainly.com/question/11006922
#SPJ1
Answer:
C
Step-by-step explanation:
In space you have to exercise 24/7, because if you don't your bones will decay little by little, the same goes for earth, it is a condition that happens if you don't move or exercise.
If possible; can I get brainliest, I mean if it's correct
Answer:
232 in^2
Step-by-step explanation:
80 + 80 + 20 + 20 + 16 + 16 = 232
Check previous answer for better explanation!
Answer:
Step-by-step explanation:
Remark
The editor must have brackets put around the denominator when there are 2 terms.
That means I think the question is (√5) / (√8 - √3). If this is incorrect, leave a note.
To rationalize the denominator, you must multiply numerator and denominator by the conjugate (√8 + √3).
Solution
√5 * (√8 - √3) / ( (√8 - √3) * (√8 + √3) )
I don't think there is any point in removing the brackets in the numerator. Just leave it.
The denominator is a different matter.
denominator = ( (√8 - √3) * (√8 + √3) )
√8 * √8 = 8
√8 * √3 = √24
- √3 * √8 = - √24
-√3 * √3 = - 3
Take a close look at the 2 middle terms. They cancel out because one of them is plus and the other minus.
What you are left with is 8 - 3 = 5
So the final answer is
√5 * (√8 - √3)
=============
5
Answer:
y = -(2/3)x + 3
C
Step-by-step explanation:
The slope of the equation that was given is - 2/3
The slope in a slope intercept equation is the number in front of the x when the value of the number in front of the y = 1 and x and y are on opposite sides of the equal sign. Let's translate that.
The original equation is y = -(2/3)x + 5/3
- y and x have to be on opposite sides of the equal sign [They are]
- The slope is the number in front of the x. That's (-2/3). That makes A incorrect.
Now you need to use the given point
The point is (-3 , 5) Put this into the equation that you have so far
y = (-2/3)x + b
y = 5
x = -3
5 = (-2/3)(-3/1) + b Substitute in the givens
5 = (-2 * -3)/3 + b Multiply -2 * - 3 = 6
5 = 6/3 + b Divide the 6 by 3
5 = 2 + b Divide
5 - 2 = b Subtract 2 from both sides
3 = b Switch sides
b = 3
Answer y = (-2/3)x + 3 or C